P-175 Pleiotropic Effects of Novel Functional LRRK2 Variation on Crohn's Disease and Parkinson's Disease Risk. (March 2016) - Hui, Ken; Fernandez-Hernandez, Heriberto; Hu, Jianzhong; Pankratz, Nathan; Rivas, Manuel; Carmi, Shai; Haritunians, Talin; Atzmon, Gil; Brant, Steven; Daly, Mark; Duerr, Richard; McGovern, Dermot; et al.
Abstract : Background: The genomic region on chromosome 12q12 containing leucine-rich repeat kinase 2 (LRRK2) includes major association signals for both Crohn's disease (CD) and Parkinson's disease (PD). Numerous functional roles have been reported for LRRK2 including autophagy, an important process believed to be involved in pathogenesis of CD. Importantly, relatively uncommon, non-synonymous variation in this region demonstrates major allele frequency differences between Ashkenazi Jewish (AJ) and non-Jewish European ancestry (NJ) populations. Thus far, no systematic analysis of this locus in association with CD has been conducted. Therefore, we sought to parse potential causal variants underlying CD association, to compare the roles of such variants against those implicated in PD, and to contrast the results in the AJ and NJ populations. Methods: Using an exome sequencing-based semi-custom array, we first conducted genotyping in 1477 independent AJ CD cases and 2614 AJ controls. We then performed imputation using sequencing and genotype data from 20, 479 CD cases, PD cases, and healthy controls of AJ and NJ ancestry to identify additional variants within the LRRK2 locus associated with a shared risk of CD and PD. To examine the role of the top LRRK2 association signals in the process of autophagy we performed in vitro studies on monocyte-derived macrophages from 13 AJ CD patients (3 N2081D carriers, 4 N551K carriers, 5 non-carriers, and 1 carrier of both coding changes, who was treated as a non-carrier due to the presumed opposing effects of the 2 mutations). Results: We detected 2 independent novel CD association signals at the coding non-synonymous mutations N2081D, conferring CD risk (OR = 1.7, P = 4.3 × 10 −8 ), and N551K, a protective variant (OR = 0.72, P = 1.4 × 10 −6 ). Similar results were also observed in an independent NJ cohort (OR = 1.6, P = 2.1 × 10 −6 and OR = 0.89, P = 5.1 × 10 −2, respectively). Importantly, both mutations were previously linked to PD, with the same magnitude and direction of effect. The G2019S coding change, strongly associated with PD, showed no evidence of association with CD. Further analyses of the imputed data showed a broad CD-association peak tagged by N2081D and additional extensive genetic pleiotropy between CD and PD within the extended LRRK2 locus, with higher minor allele frequencies in the AJ compared to NJ individuals. To test whether the novel CD-associated LRRK2 mutations affect the process of autophagy we compared the mean fluorescent intensity between genotype-specific human monocyte-derived macrophages following a pulse of lysosensor (PBS-treated versus media control). We observed an attenuated sensitivity to stress in N2081D-carrier cells and an increased sensitivity in carriers of the protective N551K mutation ( P = 0.04, order-constrained ANOVA), suggesting impaired lysosomal acidification in N2081 carriers, which could impact protein degradation and turnover of the destroyed cell organelles in immune cells. Conclusions: We identified 2 non-synonymous mutations in the LRRK2 gene significantly associated with CD risk that may play a functional role in the process of autophagy. In addition, we demonstrated extensive pleiotropy between CD and PD risk within the LRRK2 locus. These findings have significant implications for molecular targeting of LRRK2 for the treatment of CD and PD.